Real-world clinical outcomes of patients with CLN2 disease treated with cerliponase alfa - Schulz, Angela; Schwering, Christoph; Wibbeler, Eva; Westermann, Lena Marie; Hagenah, Luca; Lezius, Susanne; Jha, Ashok; Hunt, Abigail; Slasor, Peter; Reisewitz, Pascal; Nickel, Miriam (Frontiers in Neurology, 2025)
IntroductionThis study assessed the real-world effectiveness and safety of the enzyme replacement therapy (ERT), cerliponase alfa, to treat neuronal ceroid lipofuscinosis type 2 (CLN2) disease.MethodsData from the DEM-CHILD database were analyzed, comparing patients who initiated ERT outside clinical trials with natural history (NH) controls. Treated patients were matched 1:1 with NH controls on baseline age and combined motor-language (ML) score on the CLN2 clinical rating scale. Rate of ML score decline, time to unreversed 2-point decline or score of 0, and time to unreversed score of 0 were assessed. Safety was assessed in treated patients.ResultsTwenty-four ERT-treated patients were eligible (mean [SD] follow-up: 106.7 [64.1] weeks); 21 matched to a NH control, with baseline mean (SD) age of 4.7 (1.9) years and mean (SD) ML score of 3.9 (1.6) points. ERT-treated patients had reduced likelihood of an unreversed ML 2-point decline or score of 0 (HR 0.08; 95% CI 0.02, 0.28; p < 0.0001), and unreversed ML score of 0 (HR 0.07; 95% CI 0.01, 0.40; p = 0.003) versus NH controls. Mean (SD) rate of ML score decline was 0.46 (0.43) versus 1.88 (1.45) points/48 weeks for ERT-treated and NH groups, respectively (mean difference: 1.42; 95% CI 0.74, 2.10; p = 0.0003). Sixteen patients (67%) had treatment-related adverse events; the most common were pyrexia (50%), vomiting (33%), and nausea (21%). No ERT-treated patients died.DiscussionCerliponase alfa for real-world CLN2 disease treatment slowed decline in motor and language function and demonstrated an acceptable safety profile.